Pengaruh Kinerja Pengawas Sekolah Bidang Akademik, Supervisi Akademik Kepala Sekolah Dan Kompetensi Pedagogik Guru Dalam Pembelajaran IPA Terhadap Mutu Pembelajaran di SD Se-Kabupaten Halmahera Barat. - Marasabessy, Apridayani (Peneliti.net, 2023)
This research was conducted at an elementary school in West Halmahera Regency. The research procedure uses a survey procedure with a quantitative research approach. Meanwhile, the research takes the form of Descriptive Research and Verificative Explanation research with the time horizon of the information being cross-sectional which reflects a reflection of a condition at a certain time. To test the research hypothesis, the statistical procedure of path analysis (path analysis) was used using IBM SPSS version 23 computer software services. The test results showed that simultaneously the performance of school supervisors in academic areas, the academic supervision of school principals and the pedagogical competence of teachers in science learning had an influence on the quality of learning. of 0.070. Meanwhile, partially the influence of the performance of school supervisors in the academic field on quality is 0.057, the influence of the principal's academic supervision on the quality of learning is 0.133, the influence of teachers' pedagogical competence in science learning on the quality of learning is 0.193. It is recommended that school supervisors improve further in terms of guidance, mentoring, assessment and monitoring of learning in the classroom, school principals are expected to be able to carry out academic supervision activities proactively and better, teachers in science learning must further improve their competence, especially pedagogical competence